PELATIHAN METODE PEMBELAJARAN ONLINE DI KABUPATEN SIDRAP - Irvan, Nurmiati; Rais, Muh; Syarif, Irwan; Putri, Andi Nur (Universitas Patria Artha, 2023)
The existence of this pandemic makes students learn from home so that teachers need to create quality learning activities from home and do not cause boredom for students, for that teachers are expected to be able to apply online learning, of course, they must combine several learning methods. Messages or information that will be conveyed by the teacher through online learning requires methods with media and tools that are able to streamline the achievement of the learning objectives that have been set. The problems faced by partners in community service activities include the lack of knowledge and skills of teachers, especially in the Sidrap Regency Unit regarding online-based learning methods and media so that teachers still present material conventionally, which implies that learning objectives are difficult to achieve. The purpose of this training activity is to improve the knowledge and skills of teachers, especially in the Sidrap Regency Unit regarding online-based learning methods and media, through the use of zoom and mentimeter applications as well as to improve the ability of teachers to innovate using information technology and adapt to various learning methods to increase interactive between students with teachers in learning activities. The stages of this activity begin with administrative arrangements, registration of participants, implementation of training, training simulations and ends with follow-up. This training was carried out for 2 (two) days with fairly solid material, but the participants of the teachers in the Sidrap Regency education unit who had been assigned by the Sidrap Regency Education and Culture Office looked very enthusiastic in following all the material presented from opening to closing. The implementation of the training resulted in the expected outcomes, namely increasing knowledge about the use of the zoom application and they were even enthusiastic about learning about other applications that could be used for learning. The expected outcomes of this community service activity are focused on increasing the ability of teachers to use various online learning media methods, especially the use of zoom and mentimeter applications to support the learning process.Keywords: online learning, zoom, mentimeter, covid-19